Adolescent vulnerability to cardiovascular consequences of chronic social stress: Immediate and long-term effects of social isolation during adolescence - Cruz, Fábio C. [UNESP]; Duarte, Josiane O. [UNESP]; Leão, Rodrigo M. [UNESP]; Hummel, Luiz F. V. [UNESP]; Planeta, Cleopatra da Silva [UNESP]; Crestani, Carlos C. [UNESP] (Wiley-Blackwell, 2015)
It has been demonstrated that disruption of social bonds and perceived isolation (loneliness) are associated with an increased risk of cardiovascular morbidity and mortality. Adolescence is proposed as a period of vulnerability to stress. Nevertheless, the impact of chronic social stress during this ontogenic period in cardiovascular function is poorly understood. Therefore, the purpose of this study was to compare the impact in cardiovascular function of social isolation for 3 weeks in adolescent and adult male rats. Also, the long-term effects of social isolation during adolescence were investigated longitudinally. Social isolation reduced body weight in adolescent, but not in adult animals. Disruption of social bonds during adolescence increased arterial pressure without affecting heart rate and pulse pressure (PP). Nevertheless, social isolation in adulthood reduced systolic arterial pressure and increased diastolic arterial pressure, which in turn decreased PP without affecting mean arterial pressure. Cardiovascular changes in adolescents, but not adults, were followed by facilitation of both baroreflex sensitivity and vascular reactivity to the vasodilator agent acetylcholine. Vascular responsiveness to either the vasodilator agent sodium nitroprusside or the vasoconstrictor agent phenylephrine was not affected by social isolation. Except for the changes in body weight and baroreflex sensitivity, all alterations evoked by social isolation during adolescence were reversed in adulthood after moving animals from isolated to collective housing. These findings suggest a vulnerability of adolescents to the effects of chronic social isolation in cardiovascular function. However, results indicate minimal cardiovascular consequences in adulthood of disruption of social bonds during adolescence. © 2015 Wiley Periodicals, Inc. Develop Neurobiol, 2015.
Keywords: Baroreflex; Blood pressure; Heart rate; Ontogeny; Stress; Vascular reactivity